Modern local therapy of rheumatic diseases - L. N. Denisov; E. S. Tsvetkova; N. A. Shostak; E. I. Schmidt (Лечащий Врач)
The data on application of drugs for local therapy in rheumatic diseases, including transdermal therapy method were presented. The results of prospective randomized multi-center placebo-controlled studies were given.